The Analysis of Idiomatic Expressions Found in “Alice’s Adventure in Wonderland and Through To The Looking Glass” - Ni Mentari Sonia Kristin; I Putu Eka Suardana; Ni Nyoman Ayu Tri Hidayanti (Universitas Bali Dwipa, 2025)
This research aims to analyze the types of idioms and meanings in the novel entitled Alice Adventure in Wonderland and Through the Looking Glass. Idiomatic expressions are part of the elements of the English language, it needs to be mastered by Englishlearners because idioms are often found orally and in writing and communication. With the explanation above, Novel Alice In Wonderland can be used as a source for learning idiom because this novel is written in English language like in explain above idiomatic expression are part of the elements of the English language. This study was used qualitative descriptive method to analysis idiomatic expression on Alice Adventure in Wonderland and Through the Looking Glass. The researcher used the theory from Adelnia & Dastjerdi (2011) to find out form of idiomatic expression and the theory from Fernando (1996) to analyze meaning of idiomatic expression. The result of this research based on the data finding the total of form idiomatic expression are 60 idiomatic expressions. So, total of classified of form idiomatic expression is 10 colloquialism, 2 proverbs, 4 slang, 2 Allusion, 42 phrasal verbs. Based on the data there finding the total of meaning idiomatic expression are 60 idiomatic expressions. So, total of classified of type meaning idiomatic expression is 29 transparent idioms, 11 semi-transparent idioms, 12 semi-opaque idioms, 8 opaque idioms.